A review on the state-of-the-art technologies of electric vehicle, its impacts and prospects - Yong J.Y.; Ramachandaramurthy V.K.; Tan K.M.; Mithulananthan N. (Elsevier Ltd, 2023)
Charging (batteries); Climate change; Crashworthiness; Electric power transmission networks; Electric vehicles; Vehicles; Battery chargers; Charging managements; Economical benefits; Renewable energies; Smart grid; State-of-the-art technology; Vehicle integration; Vehicle to grids; Smart power grids